Prevalence and Predictor of Nonalcoholic Steatohepatitis (NASH) in Nonalcoholic Fatty Liver Disease (NAFLD) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Fatty liver is a common cause of chronic liver disease in developed as well as developing countries.We have designed this study to estimate the prevalence and predictors for non alcoholic steatohepatitis (NASH) in non alcoholic fatty liver disease (NAFLD). We have included 493 patients with sonographic evidence of fatty change in liver and 177 of them had done liver biopsy for histopathological study. Other causes of liver disease and alcohol consumption were excluded. Metabolic syndrome and biochemical and anthropometric evaluation was done. Females were predominating 250 (57.0 %). Centrally obese 422 (96.2 %) was more than over all obesity330 (75.1%). NASH was absent in 10 (5.6%) cases and diagnostic of NASH was 75 Journal of Bangladesh College of Physicians and Surgeons Vol. 32, No. 2, April 2014 (42.4 %).Presence of diabetes could significantly (p = 0.001) predicted NASH. Age, sex, BMI, waist circumference, Serum HDL,triglyceride, insulin resistance index, hypertension, metabolic syndrome could not predict NASH. Serum GGT level was significantly (p = 0.05) higher in NASHwith a sensitivity of 45 % and specificity of 68 % only. Serum ALT and AST level could not detect NASH. Females were predominant sufferer of NAFLD in Bangladesh. Prevalence of NASH was much higher42.4%. Diabetes was the main predictor of NASH. GGT was the only biochemical indicator of NASH. We recommend liver biopsy in NAFLD with diabetes and raised GGT.J Bangladesh Coll Phys Surg 2014; 32: 71-77